The Challenges of Enhancing Participation in Urban Community Empowerment (The Case of Community Empowerment Program for Villages (PPMK) Implementation in 4 Villages in Jakarta) - Ahmad Anshori; Irfan Ridwan Maksum; Linda Darmajanti (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2017)
Characteristics of DKI Jakarta as Indonesian capital with a rich diversity of people from various social, cultural, and economic backgrounds, have challenging implication for participatory community empowerment. This is proven by low participation level in community affairs in the province. This research aims to assess factors responsible for low participation in community empowerment in urban areas and identify measures to improve it.  The research was based on a qualitative methods in the Village Community Empowerment Program (PPMK) implemented in KampungRawa, Kalibaru, and Tanjung Duren Melawai in DKI Jakarta, Indonesia. The selection of the administrative villages was based on Social Insecurity Potential Index (IPKS) which portrays an overview of urban social structure. Research results showed that low  participation in community affairs is attributable to the normative nature of  participation, non-compliance of  targeted groups in  certain areas, lack of information, weak public institutions (Village Consultative Council/LMK), lack of adequate support from  local leaders (Chief of Neighborhood Association (RT) and Chief of Community Association (RW)), and absence of  management training programs. Moreover, low participation is exacerbated by low public awareness about the environment. Thus, efforts that can be undertaken include enhancing the role of the   Government, implementing e-governance by RT and RW neighborhood heads as the driving force and representatives of the community.